COMPUTER RESEARCH OF FOAMGENERATING PROCESS IN LIQUID AND GAS EJECTION DEVICE - Савик, В. М.; Нестерець, Т. О. (Academic journal Industrial Machine Building Civil Engineering, 2017)
There is a brief analysis of ejection devices that are seized in the process of influx induce of reservoir fluid during wells exploration. There have been analyzed the computer investigations of introduced device and made recommendations on its constructive elements. Keywords:wells exploration, liquid and gas ejection device, computer researhes.